MENGAKHIRI DIKOTOMI ILMU DALAM DUNIA PENDIDIKAN - Bisryi, Hasan (Forum Tarbiyah, 2009)
The separation of religion and general science has been proven to bear negative things for the future of people since by general knowledge only (both natural sciences and social sciences) has weaknesses. Similarly, religious knowledge only proves to be the same. Therefore, both must be congregated, not just give the label of Islam on these sciences, but make religion as the underlying value of every science.